Factors Leading to Early Marriages Amongst Women at Chitseka Area, Traditional Authority Chitseka, Lilongwe District - James, Dyson (Kamuzu University of Health Sciences, 2022)
This study was a descriptive, quantitative study, which was conducted at Chitseka Area, Traditional Authority Chitseka in Lilongwe District. The purpose of this study was to explore factors that may lead to early marriages amongst women at Chitseka area. Self- care deficit model was used as a conceptual frame work. A sample of 30 women was used. The study used convenience sampling method. A questionnaire with 1closed ended questions was used to collect data. A computer programme called spss was used to analyse the collected data. The study indicated that early marriages are due to poverty, school drop out and other cultural traditions like initiation of young children and the payment of lobola. It has also been demonstrated that there is a significant lack of knowledge on the part of women on the consequences of early marriages. Some of the consequences of early marriage which were found are neonatal death, puerperal and neonatal sepsis, obstetric fistulas, perpetual poverty and unemployment.